The Extracellular Domains of GluN Subunits Play an Essential Role in Processing NMDA Receptors in the ER - Horak, Martin; Barackova, Petra; Langore, Emily; Netolicky, Jakub; Rivas-Ramirez, Paula; Rehakova, Kristyna (Frontiers in Neuroscience, 2021)
N-methyl-D-aspartate receptors (NMDARs) belong to a family of ionotropic glutamate receptors that play essential roles in excitatory neurotransmission and synaptic plasticity in the mammalian central nervous system (CNS). Functional NMDARs consist of heterotetramers comprised of GluN1, GluN2A-D, and/or GluN3A-B subunits, each of which contains four membrane domains (M1 through M4), an intracellular C-terminal domain, a large extracellular N-terminal domain composed of the amino-terminal domain and the S1 segment of the ligand-binding domain (LBD), and an extracellular loop between M3 and M4, which contains the S2 segment of the LBD. Both the number and type of NMDARs expressed at the cell surface are regulated at several levels, including their translation and posttranslational maturation in the endoplasmic reticulum (ER), intracellular trafficking via the Golgi apparatus, lateral diffusion in the plasma membrane, and internalization and degradation. This review focuses on the roles played by the extracellular regions of GluN subunits in ER processing. Specifically, we discuss the presence of ER retention signals, the integrity of the LBD, and critical N-glycosylated sites and cysteine bonds within the NMDAR subunits, each of these steps must pass quality control in the ER in order to ensure that only correctly assembled NMDARs are released from the ER for subsequent processing and trafficking to the surface. Finally, we discuss the effect of pathogenic mutations within the extracellular domains with respect to ER processing, as well as the functional consequences in the CNS.